Characterization of Mycobacterium tuberculosis-specific Th22 cells in HIV-TB co-infection - Makatsa, Mohau Steven (Division of Medical Virology, 2020)
Tuberculosis (TB) remains the infectious disease causing the greatest global mortality, with an estimated 10 million incident cases of TB and 1.45 million deaths in 2018. Although there is a cure for TB, the success of the treatment is hampered by multidrug resistant TB and HIV infection. There is an urgent need for an effective TB vaccine to prevent ongoing transmission. The development of a new and efficacious TB vaccine will likely be dependent on our understanding of protective immunity to TB. Although it is well established that Th1 cells are crucial in the response against Mycobacterium tuberculosis (Mtb), Th1 cytokines may not be sufficient to control Mtb infection. A major focus of this thesis is the contribution of an understudied Th subset in Mtb immunity, namely Th22 cells, producing the cytokine IL-22. IL-22 functions to preserve mucosal barriers and induce antimicrobial peptides, contributing to protective immunity to a range of extracellular and intracellular bacteria. A recent study in IL-22-deficient mice described a protective role for IL-22 during the development of TB. In humans, soluble IL-22 has been detected at sites of extra-pulmonary tuberculosis (TB), and a polymorphism in the IL-22 promoter has been linked to TB susceptibility. However, much remains to be understood about Th22 cells and their role in protective immunity to Mtb. In this study, we investigated the contribution of Th22 cells to TB immune responses by providing a detailed characterisation of Mycobacterium tuberculosis-specific Th22 cells in latent TB infection (LTBI), TB disease and HIV co-infection, using flow cytometric techniques. In Chapter 2, we optimised detection of IL-22 and determined the factors that contribute to Mtb-specific IL-22 production by CD4+ T cells, as well as characterising some aspects of Th22 cell biology. In Chapter 3, we examined the impact of TB disease and HIV infection on Th22 cells, compared to Th1 and Th17 cells. Finally, in Chapter 4, we explored Mtb-specific cytokine production by CD8+ T cells and CD4+ T cells following Mtb peptide stimulation, and the effect of TB disease and HIV infection. We detected significant IL-22 production from CD4+ T cells in healthy individuals following whole blood stimulation with Mtb whole cell lysate (MtbL). However, IL-22 responses were poorly detectable when peripheral blood mononuclear cells (PBMC) were stimulated with MtbL. Therefore, we sought to investigate conditions that influence IL-22 detection in whole blood and PBMC, and characterise Th22 cells further. We found that PBMC are able to produce IL-22 in response to Mtb but appear to lack the physiological environment for optimal induction of IL-22. We also discovered that TCR blocking inhibited Mtb-specific IL-22 production, suggesting that responses are stimulated through recognition of Mtb antigen by the TCR, rather than through bystander activation. IL-22 is produced by CD4+ T cells that appear to be conventional, rather than MAIT, γδ or iNKT cells. Indeed, analysis of the TCR clonality using vβ repertoire typing revealed similar repertoire usage between IL-22, IFN-γ-producing CD4+ T cells, and total CD4+ T cells. Overall, these data shed more light on the biology of IL-22-producing CD4+ T cells. Next, we examined the effects of HIV infection and TB disease on the magnitude, memory profile and activation phenotype of Mtb-specific Th22 cells, compared them to Th1 and Th17 cells. Blood samples were collected from 72 individuals classified into four groups based on their HIV-1 and TB status, namely HIV-/LTBI, HIV+/LTBI HIV-/active TB and HIV+/active TB. Blood was stimulated with MtbL and analysed for cytokine production using multiparameter flow cytometry. We observed similar frequencies of IL-22 to IFN-γ-producing CD4+ T cells in LTBI. Mtb-specific Th22 cells were reduced to a greater extent than Th1 cells by a combination of HIV infection and TB disease. Th22 cells demonstrated differences in their memory and activation phenotype compared to Th1 and Th17 cells. In the context of active TB, Th1 cells were characterised by a high expression of the activation marker HLA-DR. In contrast, Th22 cells did not demonstrate activation using this marker during TB disease. Similarly, Th1 cells were more differentiated in TB disease irrespective of HIV status, while there was no difference in the memory phenotype of Th22 cells during different disease states. Finally, we characterised Mtb peptide-specific CD4+ and CD8+ T cell responses in LTBI, active TB and HIV infection. CD4+ T cells did not produce detectable IL-22 when blood was stimulated with Mtb peptides, and there was also no IL-22 response from CD8+ T cells. Th1 cytokines IFN-γ and TNF-α were detectable from CD4+ and CD8+ T cells in response to Mtb peptides. Consistent with previous studies, there was a higher proportion of individuals with detectable CD8+ responses during active TB and HIV co-infection compared to HIV-infected LTBI individuals, but no difference is the magnitude of response was observed. Interestingly, HIV infection and TB disease induced similar levels of activation in Mtb-specific CD8+ compared to CD4+ T cells. Moreover, active TB and HIV co-infection impaired memory differentiation of Mtb-specific CD8+ T cells towards a less differentiated profile, compared to LTBI. These results confirm that both CD4+ and CD8+ T cells contribute to TB immune responses. In summary, we confirm that Th22 cells constitutes a substantially portion of CD4+ T cell response to Mtb . IL-22 appears to be produced by conventional CD4+ T cells but may require specific antigen presentation requirements to optimally induce its production. Interestingly, HIV infection during TB disease led to a near absence of Th22 cells in blood. Our results warrant further study of the role of Th22 cells in TB immunity, which may lead to insights that could assist the development of an effective vaccine against TB.